Turnerjeva doba - Melik, Vasilij (Studia Historica Slovenica, 2001)
The author, in this contribution, depicts the time in which Dr. Pavel Turner lived and worked. As all the periods in the constitutional life of Austria and of Slovene political development after the February patent are sufficiently known, described and studied, the author touched on a somewhat less treated problem of the period the problem of the growth of our intelligentsia
Keywords: biografije; izobraženci; politična zgodovina; slovenska inteligenca; Turner, Pavel; znameniti Slovenci